Editorial - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 2010)
Today, the Engineering Education system appears to be in a melting pot .. The apex bodies like the AICTE, the UOC and other bodies which are in place for more than a few decades, it is reported, are to be dismantled and replaced by a single regulatory body. Whether the system was wrong or the persons handling these bodies were at fault, nothing is known. How the new set up will take care of the drawbacks of the earlier set up, has not been explained. When the Engineering Education Faculty finds itself in this precarious situation, how should it respond?